2017
DOI: 10.2337/dc16-2516
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in a Large Dementia Cohort: Clinical Characteristics and Treatment From the Swedish Dementia Registry

Abstract: OBJECTIVEWe aimed to investigate the differences in clinical characteristics and pharmacological treatment associated with the presence of diabetes in a large cohort of patients with dementia.RESEARCH DESIGN AND METHODSA cross-sectional registry-based study was conducted using data from the Swedish Dementia Registry (SveDem). Data on dementia diagnosis, dementia type, and demographic determinants were extracted from SveDem. Data from the Swedish Patient Register and Prescribed Drug Register were combined for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…Studies have revealed that individuals with dementia were more likely to be diagnosed with diabetes . Another study indicated that diabetes was associated with a lower age of dementia diagnosis, suggesting the need for optimal dementia treatment . Furthermore, patients with dementia exhibited a higher risk of circulatory system diseases (Table ); the rule “circulatory system→dementia” also represented the association between circulatory diseases and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that individuals with dementia were more likely to be diagnosed with diabetes . Another study indicated that diabetes was associated with a lower age of dementia diagnosis, suggesting the need for optimal dementia treatment . Furthermore, patients with dementia exhibited a higher risk of circulatory system diseases (Table ); the rule “circulatory system→dementia” also represented the association between circulatory diseases and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…5,28 Another study indicated that diabetes was associated with a lower age of dementia diagnosis, suggesting the need for optimal dementia treatment. 29 Furthermore, patients with dementia exhibited a higher risk of circulatory system diseases (Table 3); the rule "circulatory system→dementia" also represented the association between circulatory diseases and dementia. The study revealed that stroke, atherosclerosis, and hypertension were frequent comorbidities among patients with dementia.…”
Section: Number Of Patients With and Number Of Patients Withmentioning
confidence: 99%
“…Information on clinical and social risk factors, as potential mediators in the association of SEP with cognition, was initially identified based on the literature [24][25][26][27][28][29][30] and availability in the SHARE dataset. From those, we chose variables that were associated with the composite cognitive score at the level of p < 0.05 in at least 4 waves, after adjustment for age, sex, and years of education.…”
Section: Covariatesmentioning
confidence: 99%
“…Haroon et al [23] выявлено, что у пациентов с недавно диагностированным СД2 риск деменции составлял 1,16 (95% ДИ 1,15-1,18) [23] по сравнению с больными без СД. Установлено также, что деменция у пациентов с СД развивается в более молодом возрасте и чаще имеет сосудистый генез по сравнению с лицами без СД [24]. В свою очередь, КН снижают способность больных СД к адекватному контролю гипергликемии и увеличивают риск развития осложнений.…”
Section: A R T I C L E I N P R E S Sunclassified